MEASUREMENT OF RELATIVE EFFICIENCY OF SECOND KARKH EDUCATION SCHOOLS BY USING DATA ENVELOPMENT ANALYSIS (Journal of the College of Basic Education, 2020)
The research aims to measure the relative efficiency of middle and secondary schools in the second Karkh education. Therefore, the sample included 38 schools distributed in Al-Ma'mun, Rasheed, Yusufiya, Latifiyah and Mahmudiyah. Before determining which schools have sufficient economic efficiency and technical branches .and Measuring the efficiency of capacity and yield to know the economies of each school. The normal distribution was determined through the Jarque-Bera test and correlation by estimating the correlation matrix. Using Data Envelopment Analysis and the adoption of an induction directive to study the relationship between the inputs (number of teachers, total salaries, numbers of students and qualified students) and outputs (graduate students And the average degrees of mathematics and physics), the technical efficiency was estimated in constant and change revenue , with an average of 0.79 and 0.86, while the capacity efficiency reached an average of 0.80. The research concluded that the schools that achieved full efficiency were only 14 schools (36%) , And that 60% of the schools are working with increased returns of the size as the results indicated that it is possible to increase the output by 14%. Without increasing the input, there is a waste of 14%. The research recommended that decision makers should pay attention to data envelope analysis because this analysis enriches the strategic decision and diagnoses the imbalance and power .